THE RELATIONSHIP OF SERVICES AND PROMOTIONS WITH CUSTOMER SATISFACTION AT BANK BENGKULU BINTUHAN BRANCH - Zulkarnain; Siswanto; Abdul Rahman (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2020)
The target of this research is to know relation service with customer satisfaction at Bank of Bengkulu Branch Bintuhan and to know relation promotion with customer satisfaction at Bank of Bengkulu Branch Bintuhan. Method Analysis the used is correlation of spearman rank and hypothesis test. Assess rho count for the relation of service with customer satisfaction at Bank of Bengkulu Branch Bintuhan is its 0,663 meaning of strength, because correlation value reside in coefficient interval 0,600 - 0,799. While value of rho count for the relation of promotion with customer satisfaction at Bank of Bengkulu Branch its Bintuhan 0,643 meaning of strength, because correlation value reside in coefficient interval 0,60 - 0,799. Hypothesis test for the relation of service with customer satisfaction Bank of Bengkulu Branch Bintuhan obtained by value of t count = its 6,135 meaning of t count bigger than t tables of = 1,677 meaning conclusion of Ho refused is Ha accepted, its meaning there is relation of significant between service with satisfaction of client at Bank of Bengkulu Branch Bintuhan. While hypothesis test for the relation of promotion with satisfaction of Bank client of Bengkulu Branch Bintuhan obtained by value of t count = 5,814 its meaning of t count bigger than t tables of = 1,677 meaning conclusion of Ho refused Ha accepted, its meaning there is relation of significant between promotion with customer satisfaction at Bank of Bengkulu Branch Bintuhan.